Ma’badong dalam Analisis Semiotika Roland Barthes - Rahmawati Haruna (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2014)
Ma’badong is one of the Toraja ethnic culture that is still carried out. Ma’badong is one of the rituals of the Rambu Solo’ which was originally performed by adherents of Aluk Todolo confidence. Tana Toraja culture is inseparable from the early belief that the Toraja Aluk Todolo (ancestral spirits adore). This study aims to determine the meaning of denotation, connotation and myth contained in cultural Ma’badong. This type of research is a qualitative study using Roland Barthes' semiotic analysis. The research results show that Ma’badong within the meaning of denotation is derived from the Toraja language Ma' means "do", so Ma’badong means doing dances and singing Badong. Denotation meaning can only be viewed from the standpoint of empirical Ma’badong like movement, costume colors namely black, a place of execution, place, cutting the buffalo at least 3 buffaloes, duration, and poetry. Ma’badong in connotation meaning is sorrow dancing and singing held in death ceremony (Rambu Solo') to commemorate the biographies of those who died and begged blessing. Ma’badong within the meaning of myth in Barthes concept associated with abstinence and traditional stories of the past or of the mystical and the supernatural in the life of Toraja tribe cannot be denied its existence. The meaning of the myth of Ma’badong drawn from myth to not carelessly make Ma’badong, must wear a black costume for Ma’badong and sacrifice the animal in Rambu Solo’ ceremony.